DIFFERENCE OF THE CREEP RATE OF PRE-STRAINED AND NO PRE-STRAINED SUPERALLOY N07080 - Omer Beganović; Belma Fakić; Derviš Mujagić (Journal of Sustainable Technologies and Materials)
This paper describes the difference in the creep rate of pre-strained and no pre-strained samples of superalloy N07080. The primary strengthening mechanism of this superalloy is based on the precipitation of fine and coherent particles of the intermetallic γ' phase Ni3(Al,Ti) that ensure good creep resistance. In the case of additional strengthening of superalloy N07080 by warm plastic deformation, sometimes required by the automotive industry, its life in creep conditions will be significantly reduced. Performing the partial recrystallization annealing, after solution annealing and warm deformation, and before the final precipitation annealing, leads to a decrease in strength and an increase in the superalloy ductile properties and return of part of the lost creep life due to warm deformation. Because of the shorter lifetime of warm-deformed superalloy N07080 samples, their creep rate is higher than that of those not warm-deformed. The creep rate at 50 % of creep rupture life of superalloy N07080 that warm rolled by 30% deformation (1080°C/8h+30% warm def.+700°C/16h) is 12,9 times higher than the creep rate of the standard heat-treated superalloy. This creep rate reduces with increasing partial recrystallization temperature and for recrystallization temperature 1080°C it reaches values close to those that the superalloy possesses after standard heat treatment (1080°C/8h+700°C/16h).